## Solving the Equation: 0.4x = 0.4 - 2(x+2)

This article will guide you through the steps to solve the equation **0.4x = 0.4 - 2(x+2)**.

### 1. Distribute the -2

Begin by distributing the -2 on the right side of the equation:

```
0.4x = 0.4 - 2x - 4
```

### 2. Combine Like Terms

Combine the constant terms on the right side:

```
0.4x = -3.6 - 2x
```

### 3. Isolate the x Terms

Add 2x to both sides of the equation to bring all the x terms together:

```
0.4x + 2x = -3.6
```

### 4. Simplify

Combine the x terms:

```
2.4x = -3.6
```

### 5. Solve for x

Divide both sides by 2.4 to isolate x:

```
x = -3.6 / 2.4
```

### 6. Simplify the Solution

Simplify the result:

```
x = -1.5
```

### Conclusion

Therefore, the solution to the equation 0.4x = 0.4 - 2(x+2) is **x = -1.5**.